Exercise attitudes and practices among adults listed for kidney transplantation: a survey of a diverse patient cohort - Tasleem, Sadia; Patel, Kamlesh; Hodson, James; Mazhar, Farah; Bedford, Laura; Williams, Felicity R.; Jones, Simon; Armstrong, Matthew J.; Sharif, Adnan; Dabare, Dilan (Frontiers in Sports and Active Living, 2025)
BackgroundGiven the increasing age and frailty of kidney transplant candidates, there is an emerging drive to optimise patients before transplantation. Lack of exercise has been linked with poor outcomes at all stages of the transplant pathway. The aim of this study was to evaluate the attitudes and perception to exercise in such patients and assess how these practises vary by demographics.MethodsA single-centre, prospective, survey-based study was conducted on consecutive adult patients being assessed for activation on the deceased-donor kidney transplant waiting list.ResultsA total of 103 patients (65% male; 56% White ethnicity; mean age: 47.8 years) completed the survey. Of these, 42% were on haemodialysis and 24% on peritoneal dialysis. Most patients agreed/strongly agreed that exercise was important (86%) and that they would be willing to do so to optimise their health (97%). Despite this, only 56% of patients reported exercising on a regular basis. Most patients stated that they would be willing to wear exercise monitoring devices (81%). Younger (Spearman's rho: 0.20, p = 0.047) and Black/Asian ethnicity (p = 0.038) patients reported performing significantly less exercise activity than their older and White counterparts.ConclusionWhilst kidney transplant candidates have generally positive attitudes toward exercise, only around half of those surveyed reported exercising regularly. The findings of this study, including differences across age and ethnicity, would be useful to consider when designing patient-centred prehabilitation interventions to encourage exercise in this cohort.